Dismantling silos: cross-sectoral response to combating child sex trafficking and online child sexual exploitation - Martin, Jennifer; Gharabaghi, Kiaras; Donevan, Meghan (Frontiers in Psychology, 2025)
Until recently, child sex trafficking and online child sexual exploitation were treated as distinct crimes against children, leading to siloed responses from victim services, legal and policy frameworks, and law enforcement. Technology has blurred this distinction, and a cross-sectoral and multi-disciplinary response is needed as a first step to protect and respond effectively to victims. This paper presents the findings from a symposium in Toronto, Ontario, Canada in June 2024. Children’s mental health and child welfare practitioners, researchers, policymakers, child advocates, law enforcement professionals, and community members with lived experience came together to explore the current state of knowledge, policy, and practice related to technologically-assisted child sex trafficking and exploitation and gaps in responses to child victims. Using thematic analysis, we identified two overarching themes. Sector-Specific Roles & Challenges highlights the roles, challenges, and gaps across five key stakeholder domains. Cross-Sector Imperatives underscores the institutional, survivor-, and child-led leadership required to move beyond silos. We conclude with recommendations across policy, practice, and research to build coordinated, survivor-centered support systems capable of meeting the challenges of emerging technologies.